Human-Wildlife Conflicts in a Changing Climate Regime: A Multidimensional Perspective In Swagaswaga Game Reserve, Tanzania - Senkondo, Neema; Werema, Chacha; B. Mabhuye, Edmund (Tanzania Journal for Population studies and Development, 2024)
This study examines the influence of climatic and non-climatic factors on human- wildlife conflicts in Swagaswaga Game Reserve, Tanzania. A mixed research design employing both qualitative and quantitative data collection methods -- including semi-structured interviews, focus group discussions, and key informant interviews -- was used. Rainfall and temperature data for the past 30 years was obtained from the Tanzania Meteorological Authority. Quantitative data was analysed using IBM SPSS (V26), in which the Chi-square test was performed to test the association between predictors and the status of human-wildlife conflicts. A binary logistic regression model was used to determine the extent to which independent factors were associated with human-wildlife conflicts. Meteorological data on rainfall and temperature was analysed using Excel to perform a simple regression analysis. Qualitative data was analysed using the content analysis technique. The study revealed that both climatic and non-climatic factors influenced conflicts. As temperature increased significantly, evapotranspiration and scarcity of resources also increased, leading to a decline in crop yield, accelerated human-wildlife conflicts due to resource competition between wildlife and communities around protected areas. Rainfall distribution, onset, and cessation were unpredictable. Additionally, human-wildlife conflict is significantly associated with human population growth, while encroachment and reserve expansion influenced human-wildlife conflicts, though their impacts were not significant. Conclusively, climate change and rapid human population growth accelerated encroachment, causing wildlife survival threats and intensifying human-wildlife conflicts. The study recommends that the government should develop a comprehensive land use plan involving local communities in decision- making to adapt to the impacts of climate change on wildlife habitats and livelihoods.